A reference ontology approach to support global product-service production. (2017) - Palmer, Claire; Urwin, Esmond Neil; Young, Robert Ian Marr; Marilungo, Eugenia
The need to innovate and compete drives organisations to constantly seek new approaches to facilitate business and commerce. As market places become ever more globalised and digital economies grow, these organisations rely more heavily upon systems to design and deliver their products and services. Hence, when developing and operating a global production network the need for systems to interoperate between different domains and contexts within a global production network becomes paramount if organisations are to succeed. This paper puts forwards a reference ontology that has been developed to enable the interoperation of software tools involved in the global production of new product-services systems (PSS). It sets out the levels of the reference ontology, detailing closely the product-service aspects. This has been developed using a formal logic-based approach. An example knowledge base has been created from industrial end user information with queries applied to this to provide a set of results, showing the ability of the reference ontology.